2017
DOI: 10.3390/polym9090411
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Emissive Waterborne Polyurethanes Prepared from Naphthalimide Derivative

Abstract: Fluorescent and room-temperature phosphorescent (RTP) materials are widely used in bioimaging, chemical sensing, optoelectronics and encryption. Here, a series of single-component dual-emissive waterborne polyurethanes (WPUs) with both fluorescence and room-temperature phosphorescence were synthesized. Dye without halogen atom incorporated into WPUs can only exhibit fluorescence due to poor spin-orbit coupling. When bromine atom is introduced into dye, we found that WPUs can emit both fluorescence and room-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A similar phenomenon was further documented from polymer 14 (Scheme 2). [ 51 ] A new structured band similar to that in vacuo was observed when chromophore concentration increased, which was confirmed to belong to phosphorescence. Later, Zhang and co‐workers [ 52 ] found that RTP could be “switched on” when a new CT state was generated via external stimuli.…”
Section: Strategies To Fabricate Polymer‐based Room‐temperature Phosp...mentioning
confidence: 77%
“…A similar phenomenon was further documented from polymer 14 (Scheme 2). [ 51 ] A new structured band similar to that in vacuo was observed when chromophore concentration increased, which was confirmed to belong to phosphorescence. Later, Zhang and co‐workers [ 52 ] found that RTP could be “switched on” when a new CT state was generated via external stimuli.…”
Section: Strategies To Fabricate Polymer‐based Room‐temperature Phosp...mentioning
confidence: 77%
“…Introducing fluorescent dyes into polymer networks is a common protocol for the preparation of photoluminescence (PL) materials. 24,25 MDE is a natural fluorescent dye that was chemically modified into DVMDE, and it exhibits significant blue fluorescence emission under UV light at 365 nm. As expected, the prepared PMAD-x films also possessed fluorescence emission properties.…”
Section: Fluorescence Properties Of Pmdamentioning
confidence: 99%